Eksplorasi Peran Keuangan Hijau dalam Mendukung Ketercapaian Dekarbonisasi - Axel Giovanni; Galuh Witantri; Silvi Nur Rohma; Fabio Bolanda Sandy; Crescentiano Agung Wicaksono; Nurul Janah; Atikah Nur Fadlilah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to systematically synthesize the role and effectiveness of green finance in supporting decarbonization and to identify the instruments, success factors, and supporting policies for its implementation. This study adopts a quantitative approach using the Systematic Literature Review (SLR) analysis tool to obtain a comprehensive overview of the role of green finance in supporting decarbonization efforts to mitigate climate change anomalies caused by excessive carbon and greenhouse gas emissions. The research findings indicate that green finance, through instruments such as green credit, green investment, green bonds, green loans, and green equity investment, plays a significant role in reducing carbon emissions and driving the transition toward a low-carbon economy. Key factors influencing the success of green finance implementation include the level of development and characteristics of green finance, policies and regulations, green innovation and technology, as well as digital economy and FinTech. Additionally, this study highlights the importance of stakeholder roles and cross-sector collaboration in ensuring the successful implementation of green finance policies.